Market Options for Energy-flexible Industrial Consumers. Issue 1 (1st April 2022) - Bianchini, Isabella; Zimmermann, Fabian; Torolsan, Kerim; Sauer, Alexander
Abstract: It is widely accepted that industrial consumers can contribute to the goal of a cost-efficient energy sector by offering energy flexibility. The concrete and conscious actions on industrial processes ending up in a variety of consumption are named in literature "energy flexibility measures". From the consumers' point of view, the question is where the locally realizable energy flexibility measures can be offered with the highest cost reduction or profit. The identification of the most promising market segments or tariff schemes for the commercialization of energy flexibility measures, defined as "market options", is not a trivial activity due to the complex regulatory framework that characterizes the energy market. This paper aims at introducing a standard definition of market options that supports the energy-flexible customer to evaluate where the energy flexibility can be commercialized without specific knowledge of the energy market regulation. The definition is applied to the German energy market and the market options are identified. Through a price trend analysis, the market options with the highest potential for cost reduction or profit are investigated. The results show that in the German market consumers have the highest chances to reduce their energy supply costs through the market options related to network charges and energy-only market.